Le développement logistique des grandes périphéries métropolitaines : régimes (péri)urbains et privatisation silencieuse de la production des espaces logistiques - Nicolas Raimbault (Métropoles, 2017)
The multiplication of logistics establishments in the outer suburbia of large urban regions is embedded in a diversity of public actions in these spaces: transport facilities, land development and building permits. Thus, this economic development supposes a strong interdependence between economic and political spheres. This interdependence is at the heart of “urban regimes” approach (Stone, 1989) and echoes the concepts of “development regimes” (Stone, 1993) and “growth coalitions” (Logan, Molotch, 1987). Thus, this paper proposes to apply these approaches and concepts to the case of the outer suburbia of large urban regions concerned by the logistics industry development. This way, it calls for reopening the issue of the transposition of these theories from the American cities to the European cities (Le Galès, 1995) by linking the analysis of the public capacities of local governments with the analysis of the modalities of involvement of private economic actors in local public actions in the context of the financialization of commercial real estate and governance discontinuities. Eventually, through this lens, quite stable public-private coalitions which are dominated by the logistics property firms appear in the outer suburbia of the Paris city-region, which leads to a silent privatization of the production of logistics spaces.